[PP.37.23] CARDIOVASCULAR REMODELLING IN HYPERTENSIVE PATIENTS: DOES GENDER MATTER?. (September 2016) - Pierobon, V.; Tavecchia, L.; Agostinis, M.; Tandurella, N.; Grossi, A.; Mongiardi, C.; Test, L. Robustelli; Moretti, S.; Gadaleta, C.; Guasti, L.; Grandi, A.M.; Maresca, A.M.
Abstract : Objective: To investigate whether common cardiovascular risk factors act differently between genders in the development of organ damage in untreated mild hypertensive patients. To correlate also any differences in subclinical organ damage to office, 24 h and central blood pressure (BP). Design and method: We enrolled 60 women and 50 men (without cardiovascular disease or diabetes, non smokers) aged between 35 and 55 years old with mild hypertension. For the control group were enrolled 60 normotensive women and 50 normotensive men matched for age and BMI. For each subject, we evaluated office and 24 h BP. Each patient underwent arterial tonometry (central blood pressure), echocardiography (left ventricular mass, thoracic aortic diameters), carotid (intima media thickness, IMT) and abdominal aortic ultrasonography and blood tests. Results: Using a regression analysis we found an outstanding role of BMI (beta = 0.47, p = 0.0001) and central BP (beta = 0.26, p = 0.002) to predict left ventricular mass in women. In men, BMI (beta = 0.40, p = 0.001) age (beta = 0.21, p = 0.003) and 24 h SBP (beta = 0.34, p = 0.0001) seem to play a major role. Regarding thoracic aorta we found a significant correlation to central BP in both men and women (beta = 0.23, p = 0.01 and beta = 0.19, p = 0.03), whereas this association is detectable for abdominal aorta only in women (beta = 0.37, p = 0.01). Finally, in the prediction model of IMT, age and BMI were significant in both genders. In women we found a significant correlation with 24 h BP (beta = 0.20, p = 0.007), while in men with central BP (beta = 0.23, p = 0.007). Conclusions: In men target organ damage appears mainly related to age, BMI and 24 h BP. In women the role of age seems lower and CV remodelling appears also related to central BP.